Modulated Electro-Hyperthermia Facilitates NK-Cell Infiltration and Growth Arrest of Human A2058 Melanoma in a Xenograft Model - Vancsik, Tamás; Máthé, Domokos; Horváth, Ildikó; Várallyaly, Anett Anna; Benedek, Anett; Bergmann, Ralf; Krenács, Tibor; Benyó, Zoltán; Balogh, Andrea (Frontiers in Oncology, 2021)
Modulated electro-hyperthermia (mEHT), induced by 13.56 MHz radiofrequency, has been demonstrated both in preclinical and clinical studies to efficiently induce tumor damage and complement other treatment modalities. Here, we used a mouse xenograft model of human melanoma (A2058) to test mEHT (~42 °C) both alone and combined with NK-cell immunotherapy. A single 30 minutes shot of mEHT resulted in significant tumor damage due to induced stress, marked by high hsp70 expression followed by significant upregulation of cleaved/activated caspase-3 and p53. When mEHT was combined with either primary human NK cells or the IL-2 independent NK-92MI cell line injected subcutaneously, the accumulation of NK cells was observed at the mEHT pretreated melanoma nodules but not at the untreated controls. mEHT induced the upregulation of the chemoattractant CXCL11 and increased the expression of the matrix metalloproteinase MMP2 which could account for the NK-cell attraction into the treated melanoma. In conclusion, mEHT monotherapy of melanoma xenograft tumors induced irreversible heat and cell stress leading to caspase dependent apoptosis to be driven by p53. mEHT could support the intratumoral attraction of distantly injected NK-cells, contributed by CXCL11 and MMP2 upregulation, resulting in an additive tumor destruction and growth inhibition. Therefore, mEHT may offer itself as a good partner for immunotherapy.